The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1016/j.adaj.2020.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Zirconia restorations

Abstract: † 0.4% of respondents selected "Fracture of opposing teeth" and 0.4% selected "cost." Percentages may not add up to 100% owing to rounding. ‡ These respondents are a subset (n ¼ 184) who use at least some anterior zirconia restorations. § The remaining respondents selected "Yes, other reason."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Monolith zirconia’s choice for posterior teeth could be due to its high flexural strength and fracture resistance compared to the inherently brittle feldspathic porcelain, or concern of about wearing of opposing natural teeth by feldspathic porcelain [ 5 , 24 ]. A similar choice of zirconia for fabricating posterior crowns was also seen among 277 respondents in a study conducted by the ADA panel [ 25 ]. In fact, a study conducted in 2013, among dental schools in America suggested the shift of material preference from feldspathic porcelain to zirconia (80%) within a span of 10–15 years due to greater strength and clinical longevity similar to PFM [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 73%
“…Monolith zirconia’s choice for posterior teeth could be due to its high flexural strength and fracture resistance compared to the inherently brittle feldspathic porcelain, or concern of about wearing of opposing natural teeth by feldspathic porcelain [ 5 , 24 ]. A similar choice of zirconia for fabricating posterior crowns was also seen among 277 respondents in a study conducted by the ADA panel [ 25 ]. In fact, a study conducted in 2013, among dental schools in America suggested the shift of material preference from feldspathic porcelain to zirconia (80%) within a span of 10–15 years due to greater strength and clinical longevity similar to PFM [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 73%
“… 28 Esthetic limitations like translucency and shade matching affect zirconia's use in anterior restorations. 29 Zirconia-based all-ceramic crowns for molar teeth with metal antagonist occlusion should be undertaken cautiously due to risks like veneering ceramic fracture. 30 …”
Section: Discussionmentioning
confidence: 99%
“…Along with the higher cubic phase, clinicians have managed to overcome the difficulty of achieving adhesion between dental tissues and zirconia ceramics with the help of new adhesion techniques and resin cement containing adhesive monomers that can promote chemical adhesion through the reaction between acidic functional and oxide groups on the zirconia surface (Chen et al, 2014;Quigley et al, 2021). The above resulted in the clinical use of zirconia for esthetic anterior cases (Naveau et al, 2019) or as a material for anterior veneers (Lawson et al, 2021). Along with the use of multi-layered translucent monolithic zirconia ceramics, several other materials are included in the armamentarium of a CAD/CAM dental clinic.…”
Section: Introductionmentioning
confidence: 99%